The Effect of Directed Reading Thinking Activity In Cooperative Learning Setting Toward Students’ Reading Comprehension Of The Eleventh Grade Students - S. A. Kompyang Arisetyawati (Universitas Pendidikan Ganesha, 2017)
This research was aimed at investigating whether there was a significant effect on reading comprehension of the eleventh grade students who were taught by using Directed Reading Thinking Activity in Cooperative Learning Setting and who were taught by using Directed Reading Thinking Activity only. The research was an experimental research with Post-Test Only Control Group Design. The research was conducted at SMA N 3 Singaraja. The population of this research was the eleventh grade students in academic year 2016/2017 with the samples of 65 students who were selected through random sampling technique. The data were collected by using reading comprehension test. The obtained data were analyzed by using t-test assisted with SPSS 22.0. The result of the research showed that there was a significant effect on reading comprehension of the eleventh grade students in which the students who were taught by using Directed Reading Thinking Activity in Cooperative Learning Setting achieved better reading comprehension than who were taught by using Directed Reading Thinking Activity only (tobs = 4.056, p < 0.05).